Hold your horses! A typology of endurance horse-riding participants. Issue 6 (2nd November 2021) - Kruger, Martinette; Viljoen, Adam; Cronjé, Daniélle
ABSTRACT: Rationale: Limited research is available on endurance horse riding participants. Purpose: This research identified different segments of these niche participants. Methods: Self-administered questionnaires were distributed to participants during an international endurance ride held in South Africa. Based on convenience sampling, a total of 116 completed questionnaires were obtained. Five motives to participate in the race (race, challenge, intrinsic, equine performance and event experience achievement) and four behavioural involvement pursuits (passive equine pursuits, event loyalty pursuits, active equine pursuits, and health and fitness pursuits) were identified. Based on these factors, three distinct endurance horse riding participant segments were identified: Equine achievers, Equine pursuers, and Equine challengers. Findings: The findings confirm that endurance sport participants cannot be regarded as homogenous. Contributions: Endurance horse riding events can be seen as a means to facilitate and encourage additional behavioural involvement pursuits that help expand the endurance horse-riding industry in South Africa.